1996
DOI: 10.1111/j.1600-0714.1996.tb00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immunoglobulin‐synthesizing cells in human dental periapical lesions by in situ hybridization and immunohistochemistry

Abstract: Immunoglobulin (Ig) kappa (kappa) and lambda (lambda) light chain mRNA-expressing cells were investigated by in situ hybridization (ISH) to assess the local humoral immune response in human dental periapical lesions. Twenty-seven biopsy samples (17 periapical granulomas and 10 radicular cysts) were examined. Both types of light chain mRNA-positive cells were detected in formalin-fixed/paraffin-embedded tissue sections in all samples. Plasma cells showed weak to strong cytoplasmic staining with both probes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0
2

Year Published

1997
1997
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
4
10
0
2
Order By: Relevance
“…(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)). (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)).…”
Section: Introductionunclassified
“…(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)). (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)).…”
Section: Introductionunclassified
“…Although some investigators have reported immunoglobulin light chain staining in B-cell NHL using FFPE tissues (2,3), not all authors have been successful (4)(5)(6)(7)(8)(9)(10). In this report, we present and validate a HIER technique in a series of cases of B-cell NHL.…”
Section: Discussionmentioning
confidence: 89%
“…Although some have reported detectable immunoglobulin light chain staining using FFPE tissues (2,3), not all authors have been successful (4)(5)(6)(7)(8)(9)(10). Indeed, in several recent studies using paraffin immunoperoxidase to study B-cell non-Hodgkin lymphoma (NHL), polymerase chain reaction, Southern blot analysis, or flow cytometric immunophenotyping was required to demonstrate monoclonality (11)(12)(13).…”
mentioning
confidence: 99%
“…Several apparently successful methodologies have been published, most often requiring enzymatic or heat antigen retrieval, or both (2-4). Yet, the success of at least some of these protocols has been difficult to replicate (8-14). For example, our laboratory has not found the high sensitivity claimed using the procedure published by Hartford, and in fact most of the cases in the present study were negative when using that procedure in our laboratory (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It widely acknowledged to be an effective means of detecting monotypic light chain expression in plasma cells, however its efficacy in detecting the smaller amounts of immunoglobulin present on B-lymphocytes and B-cell lymphomas is still controversial. While a minority of authors report relatively reliable detection of immunoglobulin in B-cells and their neoplasms, using either enzyme digestion combined with microwave-heating antigen retrieval (5), enzyme digestion alone (6), or heat-induced epitope retrieval alone (7), the majority of investigators have not obtained similar good results (8-14). In addition, our own practical experience, both from our laboratory and reviewing diagnostic slides prepared by other laboratories, suggests that there is not widespread satisfaction with current practical light chain immunoglobulin studies.…”
mentioning
confidence: 99%